Enterprise Risk Management and IT Resources impact on Sustainable Competitive Advantage through mediating role of Knowledge Management Capability - Saleem, Syed Muhammad Umer; Taib, Che Azlan; Iteng, Rosman (Journal of Ecohumanism, 2025)
Purpose – This study seeks to determine impact of enterprise risk management (ERM) and information technology resources (ITR) on sustainable competitive advantage (SCA) through mediating role of knowledge management capability (KMC). Methodology – An investigation based on empirical research was carried out on 183 software companies in Lahore, Rawalpindi, Islamabad and Karachi, Pakistan. A self-administered survey was conducted to obtain the data from software companies. The study employed stratified random sampling for participant selection and data were analyzed through partial least squares structural equation modelling (PLS-SEM). Findings – Results revealed ERM and KMC significantly contribute to SCA. However, ITR did not directly impact SCA, yet it showed an important mediated effect on SCA through KMC. Also, KMC mediates relationship between ERM and SCA. Implications – The outcomes of this study contribute to resource based view (RBV) theory by demonstrating that ERM, ITR and KMC play pivotal roles in achieving SCA within the IT industry. Policymakers and industry leaders are encouraged to support these areas to help companies anticipate risks, optimize resources and thrive in global markets. Limitations – This study focused exclusively on private software companies located in four cities (Islamabad, Rawalpindi, Lahore and Karachi) within Pakistan. Additionally, the cross-sectional, survey-based methodology captured data only at a single point in time. Originality – The novelty of this article lies in fact that it addresses the gap in existing research through exploring effect of ERM and ITR on SCA through mediating role of KMC in Pakistani private software companies.